Identification and preliminary bioactivity screening of the marine endophytic fungus Aspergillus terreus strain BAWK-F6 derived from Algerian brown seaweed - Fodili, Assia; Debib, Aicha; Saadi, Sid Ahmed; Abdi, Azzedine; Abidi, Mohamed; Aitialeff, Khouloud; Akmoun, Rayane; Douaoui, Abdelkader (Archives of Biological Sciences, 2026)
Paper description: The algicolous endophyte fungus Aspergillus terreus BAWK-F6 isolated from brown seaweed was investigated for its bioactive potential. Integrated molecular identification and GC-MS bioactive metabolite profiling were conducted, revealing the distinctive characteristics of the strain. The crude fungal extract showed multiple bioactivities, including antioxidant, antimicrobial, antibiofilm, anti-inflammatory, and anti-urolithic activities. By providing strain-specific molecular identification and bioactivity profiles, this work enhances current knowledge of marine terreus associated with algal hosts along the Algerian coast. Abstract: Marine fungi are known for their ability to produce bioactive compounds with pharmaceutical potential. However, their growth in diverse and often extreme habitats makes laboratory cultivation difficult, thereby limiting research progress. The algicolous endophyte fungus Aspergillus terreus strain BAWK-F6 was isolated from brown seaweed Dictyota dichotoma and identified through molecular analyses. The fungal extract was evaluated for a range of biological activities. Molecular identification revealed a high genetic similarity with other A. terreus strains, and chemical analysis using gas chromatography mass spectrometry (GC-MS) identified 28 compounds. The extract demonstrated antioxidant activity, with IC₅₀ values ranging from 1.98 to 2.32 mg/mL. Antimicrobial assays demonstrated that the extract effectively inhibited a broad spectrum of Gram-negative pathogens, with minimum inhibitory concentrations (MIC) ranging from 0.625 to 1.25 mg/mL. The extract also exhibited potent antibiofilm activity, especially against Staphylococcus aureus. It exhibited anti-inflammatory activity by inhibiting protein denaturation and stabilizing red blood cell membranes, as well as anti-urolithic potential by suppressing the formation of calcium phosphate crystals. These findings highlight the therapeutic promise of Aspergillus terreus BAWK-F6 as a source of bioactive compounds with potential applications in pharmacology and biotechnology.